Highly Crystallized Brilliant Polymeric Photonic Crystals via Repulsion‐Induced Precipitation Assembly toward Multiresponsive Colorimetric Films. Issue 11 (25th August 2016) - Tan, Peng‐Feng; Wang, Cai‐Feng; Wang, Xiao‐Qiao; Ji, Wen‐Qing; Chen, Min; Chen, Su
Abstract : Brilliant high‐crystalline photonic film is created via a fast repulsion‐induced precipitation assembly process. Taking advantage of super‐high concentration of highly charged colloids, monochromatic close‐packed photonic films are formed within seconds featuring narrow full width at half maximum, broad stop‐band shift, high response rate, good sensitivity and reversibility. These ultrathin flexible films can serve as multiresponsive colorimetric materials for visually detecting diverse species. Abstract : The construction of high‐quality 3D polymeric photonic crystal (PC) films featuring fascinating tunable optical properties in a facile and time‐efficient way remains a major concern. Herein, the rapid assembly of highly crystallized brilliant flexible 3D polymeric PC films and their application for multiresponsive colorimetric sensing are demonstrated. Monochromatic PC films with remarkably distinct structural color, narrow half‐band width (27 nm), and broad tunability of band‐gaps (from blue to red) are generated within seconds from highly concentrated and charged colloids (51 vol%, −57.6 mV) embedded in poly( N ‐isopropylacrylamide) matrix. A repulsion‐induced precipitation assembly is found to be responsible for the ultrafast formation of close‐packed PC colloidal arrays. Besides, the resultant PC films exhibit ultrasensitive and fast response to external stimuli, revealed by interesting droplet diffusion experiments. Thus these PC films can serve as efficient colorimetric sensing materials to visually determine diverse species including trace ionic strength (2.9 ppm), minor surfactant (1 × 10 −3 m ), alcohol, and pH variation (1.0–13.9).